2015
DOI: 10.1177/1069072715580418
|View full text |Cite
|
Sign up to set email alerts
|

Prestige Added to Holland’s Vocational Interest Scales for the Prediction of Medical Students’ Aspired Work Environments

Abstract: The current study examines the relative impact of vocational interests and prestige on medical students’ aspired work environments. The following areas were included: family doctor, specialist in a private practice, specialist in a hospital, scientific researcher, and dentist. We also added the category “undecided students.” The sample consisted of 788 medical students in their preclinical years. Multinomial logistic regression analysis showed that the impact of vocational interests and prestige varied as a fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 38 publications
(74 reference statements)
0
1
0
1
Order By: Relevance
“…Em todos estes estudos há convergência quanto à orientação motivacional das raparigas no domínio da relação pessoal e das atividades artísticas e do envolvimento dos rapazes nas áreas da atividade física, dados, máquinas e ferramentas, tal como corroborado em diferentes amostras e culturas (e.g. Guntern, Korpershoek, & Werf, 2016;Iskander et al, 2013;Prime et al, 2015). O presente estudo tem a mais-valia de analisar interesses e competências percebidas na infância e corrobora o género como determinante na formação do autoconceito infantil (Bussey & Bandura, 1999;Gottfredson, 1981;1996), apesar de se salientarem outros indicadores de natureza académica, familiar e social na formação do autoconceito (Laranjeira & Teixeira, 2012;RubieDavies, 2006;Teixeira & Ferreira, no prelo).…”
Section: Associação Entre Perceções De Competência Eunclassified
“…Em todos estes estudos há convergência quanto à orientação motivacional das raparigas no domínio da relação pessoal e das atividades artísticas e do envolvimento dos rapazes nas áreas da atividade física, dados, máquinas e ferramentas, tal como corroborado em diferentes amostras e culturas (e.g. Guntern, Korpershoek, & Werf, 2016;Iskander et al, 2013;Prime et al, 2015). O presente estudo tem a mais-valia de analisar interesses e competências percebidas na infância e corrobora o género como determinante na formação do autoconceito infantil (Bussey & Bandura, 1999;Gottfredson, 1981;1996), apesar de se salientarem outros indicadores de natureza académica, familiar e social na formação do autoconceito (Laranjeira & Teixeira, 2012;RubieDavies, 2006;Teixeira & Ferreira, no prelo).…”
Section: Associação Entre Perceções De Competência Eunclassified
“…In a study conducted with medical students from five universities in Austria and Switzerland, based on status and socioeconomic aspects, they rated prestige as one of the main factors influencing their choice of field of specialization. Prestige was mainly related to the desired work environments of specialists in private practice [ 10 ]. A study conducted in Turkey among resident physicians at the Medical Specialization Examination found that the common reasons for choosing the specialty were career opportunities and working conditions [ 11 ].…”
Section: Introductionmentioning
confidence: 99%